A novel missense mutation (N258S) in the KCNQ2 gene in a Turkish family afflicted with benign familial neonatal convulsions (BFNC) - (:unkn) unknown (TURKISH J PEDIATRICS, 2007)
Benign familial neonatal convulsions (BFNC) is a rare monogenic subtype of idiopathic epilepsy exhibiting autosomal dominant mode of inheritance. The disease is caused by mutations in the two homologous genes KCNQ2 and KCNQ3 that encode the subunits of the voltage-gated potassium channel. Most KCNQ2 mutations are found in the pore region and the cytoplasmic C domain. These mutations are either deletions/insertions that result in frameshift or truncation of the protein product, splice-site variants or missense mutations. This study reveals a novel missense mutation (N258S) in the KCNQ2 gene between the S5 domain and the pore of the potassium channel in two BFNC patients in a Turkish family. The absence of the mutation both in the healthy members of the family and in a control group, and the lack of any other change in the KCNQ2 gene of the patients indicate that N258S substitution is a pathogenic mutation leading to epileptic seizures in this family.
Keywords: potassium channel gene; benign familial neonatal convulsions (BFNC); mutation; POTASSIUM CHANNEL GENE; IDIOPATHIC EPILEPSY; CELLS